Sucralose, a Non-nutritive Artificial Sweetener Exacerbates High Fat Diet-Induced Hepatic Steatosis Through Taste Receptor Type 1 Member 3 - Wu, Hung-Tsung; Lin, Ching-Han; Pai, Hsiu-Ling; Chen, Yi-Cheng; Cheng, Kai-Pi; Kuo, Hsin-Yu; Li, Chung-Hao; Ou, Horng-Yih (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease globally, and it is strongly associated with obesity. In order to combat obesity, artificial sweeteners are often used to replace natural sugars, and sucralose is one of the most extensively-used sweeteners. It was known that sucralose exerted effects on lipid metabolism dysregulation, and hepatic inflammation; however, the effects of sucralose on hepatic steatosis were still obscure. In this study, we found that supplement of sucralose enhanced high fat diet (HFD)-induced hepatic steatosis. In addition, treatment of sucralose increased reactive oxygen species (ROS) generation and induced endoplasmic reticulum (ER) stress in HepG2 cells. Pre-treatment of ROS or ER stress inhibitors reversed the effects of sucralose on lipogenesis. Furthermore, pre-treatment of taste receptor type 1 membrane 3 (T1R3) inhibitor, or T1R3 knockdown reversed sucralose-induced lipogenesis in HepG2 cells. Taken together, sucralose activated T1R3 to generate ROS and promote ER stress and lipogenesis, and further lead to the development of hepatic steatosis.